Review. Patrice McSherry. La Nueva Canción Chilena. El poder político de la música, 1960 -1973. Santiago de Chile, Editorial Lom, 2017 (Palimpsesto, 2020)
Review. Patrice McSherry. La Nueva Canción Chilena. El poder político de la música, 1960 -1973. Santiago de Chile, Editorial Lom, 2017
Keywords: Review